An empirical analysis for the perceptions of Amman stock exchange's investors - Mohammad Sami Ali (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Research problem: Although the economy of Jordan witnessed dramatic volatilities and fundamental variables including market-to-book value ratio and interest rate are located at the middle of these variations; there is a lack in literature regarding the impacts of market fundamentals and dividends policies in investors' perceptions, as captured by the performance of Amman stock exchange. Research objectives: Thus, due to the power of these variables to impact investment decisions, this research aimed at scrutinizing the long and short-run causalities, which are running from market fundamentals, dividends policies, and the 2008/11 financial crisis towards investors' perceptions. Research methodology: To accomplish the core aim of this research, empirical techniques like Augmented Dickey Fuller, Johansen Co-integration, the single equation of the error correction model "ECM" and the Wald test are mainly utilized to analyze a time series data set covering the period Jan/1990-Dec/2017. Results and future recommendations: Consequently, results from ECM confirmed that the study's variables are not integrated over the long-run. Alternatively, findings from the Wald test approved that investors' perceptions as captured by the market's performance are statistically related to market fundamentals, dividends policies and the recent financial crisis. Therefore, the study concluded that ASE's investors adopt the view of Gordon (1962) and Lintner (1962) during the short-run. However, the study recommends further researchers to follow the study's models to investigate the other variables, which are impacting investors' perceptions, as well as examining the impact of financial crises in the decisions of dividends' policies.
Keywords: E44; G12; D53; G01; G21; G40; 650; market fundamentals; dividends policies; buffet indicator; M/BV; interest rates; investors' perception; ECM